The characterization of Hasan Minhaj's humor language in the daily show with trevor noah's show the best of Hasan Minhaj-Muslim Ban, women's soccer and Canada - Janitra Fullaroa Salsabil (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2022)
wt,1/ yna, c.1